Clinical diversity of MYH7‐related cardiomyopathies: Insights into genotype–phenotype correlations. Issue 3 (27th December 2018) - Hershkovitz, Tova; Kurolap, Alina; Ruhrman‐Shahar, Noa; Monakier, Daniel; DeChene, Elizabeth T.; Peretz‐Amit, Gabriela; Funke, Birgit; Zucker, Nili; Hirsch, Rafael; Tan, Wen‐Hann; Baris Feldman, Hagit
Abstract : MYH7 ‐related disease (MRD) is the most common hereditary primary cardiomyopathy (CM), with pathogenic MYH7 variants accounting for approximately 40% of familial hypertrophic CMs. MRDs may also present as skeletal myopathies, with or without CM. Since pathogenic MYH7 variants result in highly variable clinical phenotypes, from mild to fatal forms of cardiac and skeletal myopathies, genotype–phenotype correlations are not always apparent, and translation of the genetic findings to clinical practice can be complicated. Data on genotype–phenotype correlations can help facilitate more specific and personalized decisions on treatment strategies, surveillance, and genetic counseling. We present a series of six MRD pedigrees with rare genotypes, encompassing various clinical presentations and inheritance patterns. This study provides new insights into the spectrum of MRD that is directly translatable to clinical practice.